The Victoria Institute, Biblical Criticism, and the Fundamentals - Mathieson, Stuart (Zygon, 2021)
The Victoria Institute was established in London in 1865. Although billed as an anti-evolutionary organization, and stridently anti-Darwinian in its rhetoric, it spent relatively little time debating the theory of natural selection. Instead, it served as a haven for a specific set of intellectual commitments. Most important among these was the Baconian scientific methodology, which prized empiricism and induction, and was suspicious of speculation. Darwin's use of hypotheses meant that the Victoria Institute members were unconvinced that his work was truly scientific, but even more concerning for them was the specter of biblical criticism. This approach to biblical studies incorporated techniques from literary criticism, treating it as any other document. Since it also relied on hypotheses, the Victoria Institute members were similarly skeptical that biblical criticism was scientific, and spent much of their time attempting to refute it. In this way, they functioned as an incubator for the concerns that would animate the fundamentalist-modernist controversies of the early twentieth century.